Design and fabrication of a self-balancing device for food delivery - Kamardin, Nur Kamarliah; Mohd Fauzi, Alif Darwisy; Rusli, Ahmad Najmie; Yusuf, Ahmad Idzwan; Abdul Kadir @ Che Ismail, Ros Atiqah; Mohd Rodzi, Ana Syahidah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
The self-balancing device for food delivery is designed to secure food and beverages inside the delivery bags, minimizing spills and damage during rushed or winding road deliveries. Maintaining the food in perfect condition after delivery significantly enhances the customer experience. Existing food delivery literature has explored solutions like a bag carrier mounted at the back of motorcycles or worn like a backpack by the rider. However, such setups rely on motorcycle swerving, leading to potential spills and damage, especially on busy or winding routes. Moreover, this approach jeopardizes rider safety as they must balance swift delivery with keeping the food intact, potentially leading to accidents due to divided attention. This project's main objectives are twofold: first, to design an efficient self-balancing device for food delivery, and second, to analyse the mechanical systems involved in its implementation. By achieving these goals, the project aims to reduce the risk of accidents for riders while ensuring the food reaches customers in perfect condition. This project seeks to revolutionize food delivery by introducing a self-balancing device to maintain food stability during transportation.